A Staged Arthroscopic Approach to Fixation of Unstable Osteochondritis Dissecans in the Medial Femoral Condyle of the Knee Using Nonabsorbable Fixation Screws - Gowd, Anirudh K. (Arthrosc Tech, 2020)
Osteochondritis dissecans is a focal lesion of articular cartilage that can result in fragment instability with progression of early osteoarthritis. Regarding the knee joint, salvage of an unstable lesion can be achieved using arthroscopic-assisted reduction and fixation via a 2-stage process. The first involves arthroscopic fixation of the fragment using nonbioabsorbable screws, whereas the second stage performed 12 weeks later involves removal of the screws and confirmation of successful healing of the lesion. Previous studies have demonstrated excellent outcomes in patients undergoing fixation for unstable chondral lesions not amenable to conservative treatment. A critical component of successful treatment is understanding the importance of hardware placement and technique. The purpose of the Technical Note is to describe a method performing this 2-stage arthroscopic repair of an unstable chondral lesion located on the medial femoral condyle of the knee.